Maturation of human induced pluripotent stem cell-derived cardiomyocytes promoted by Brachyury priming - Parisa K. Kargaran; Armin Garmany; Ramin Garmany; Marissa J. Stutzman; Maryam Sadeghian; Michael J. Ackerman; Carmen M. Perez-Terzic; Andre Terzic; Atta Behfar (Scientific Reports)
Abstract Cardiac differentiation of human induced pluripotent stem cells is readily achievable, yet derivation of mature cardiomyocytes has been a recognized limitation. Here, a mesoderm priming approach was engineered to boost the maturation of cardiomyocyte progeny derived from pluripotent stem cells under standard cardiac differentiation conditions. Functional and structural hallmarks of maturity were assessed through multiparametric evaluation of cardiomyocytes derived from induced pluripotent stem cells following transfection of the mesoderm transcription factor Brachyury prior to initiation of lineage differentiation. Transfection with Brachyury resulted in earlier induction of a cardiopoietic state as hallmarked by early upregulation of the cardiac-specific transcription factors NKX2.5, GATA4, TBX20. Enhanced sarcomere maturity following Brachyury conditioning was documented by an increase in the proportion of cells expressing the ventricular isoform of myosin light chain and an increase in sarcomere length. Mesoderm primed cells displayed increased reliance on mitochondrial respiration as determined by increased mitochondrial size and a greater basal oxygen consumption rate. Further, Brachyury priming drove maturation of calcium handling enabling transfected cells to maintain calcium transient morphology at higher external field stimulation rates and augmented both calcium release and sequestration kinetics. In addition, transfected cells displayed a more mature action potential morphology with increased depolarization and repolarization kinetics. Derived cells transfected with Brachyury demonstrated increased toxicity response to doxorubicin as determined by a compromise in calcium transient morphology. Thus, Brachyury pre-treatment here achieved a streamlined strategy to promote maturity of human pluripotent stem cell-derived cardiomyocytes establishing a generalizable platform ready for deployment.